2010
DOI: 10.1007/s00726-010-0628-x
|View full text |Cite
|
Sign up to set email alerts
|

High-abundance proteins depletion for serum proteomic analysis: concomitant removal of non-targeted proteins

Abstract: In clinical and pharmaceutical proteomics, serum and plasma are frequently used for detection of early diagnostic biomarkers for therapeutic targets. Although obtaining these body fluid samples is non-invasive and easy, they contain some abundant proteins that mask other protein components present at low concentrations. The challenge in identifying serum biomarkers is to remove the abundant proteins, uncovering and enriching at the same time the low-abundance ones. The depletion strategies, however, could lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
157
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(164 citation statements)
references
References 42 publications
4
157
0
Order By: Relevance
“…This approach, however, often results in the loss of potentially biologically relevant proteins that are bound to the high-abundance proteins being depleted whether this be a simple albumin depletion, or a depletion of the top 6-12 hyper-abundant proteins. [22,23] Using the TMTcalibrator ™ approach, albumin, for example, is still detected and measured in the CSF as the protein is still present but is not dominating the MS acquisition. In this study we detected albumin, as expected, in the six CSF samples and also observed the expected regulation between AD and control CSF samples.…”
Section: Tmtcalibratormentioning
confidence: 99%
“…This approach, however, often results in the loss of potentially biologically relevant proteins that are bound to the high-abundance proteins being depleted whether this be a simple albumin depletion, or a depletion of the top 6-12 hyper-abundant proteins. [22,23] Using the TMTcalibrator ™ approach, albumin, for example, is still detected and measured in the CSF as the protein is still present but is not dominating the MS acquisition. In this study we detected albumin, as expected, in the six CSF samples and also observed the expected regulation between AD and control CSF samples.…”
Section: Tmtcalibratormentioning
confidence: 99%
“…However, performing discovery proteomics is challenging because of the wide dynamic range of plasma proteins and because of the interference from large, multiply charged proteins such as albumin, apolipoprotein A1, and C‐reactive protein (Geyer, Holdt, Teupser, & Mann, 2017). Attempts to address this challenge by depletion of highly abundant proteins from plasma samples have generated conflicting results, with some suggestions that proteins in depleted samples are no longer representative of the those in the original sample (Bellei et al., 2011). An alternative approach is to use the SOMAscan assay, a technology that uses slow off‐rate modified aptamers (SOMAmer)‐based capture to quantify multiple proteins in human biological liquids, including plasma (Baird, Westwood, & Lovestone, 2015; Di Narzo et al., 2017; Menni et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example it has been shown that the depletion of albumin from human plasma can also remove low abundance proteins such as cytokines (Granger et al, 2005). More recent studies (Bellei et al, 2010) have also concluded that removal of high-abundance proteins can result in a loss of non-targeted, less abundant proteins. Obviously unintentional and unknowing loss of low abundance proteins is a cause for concern in the search for biomarkers of disease.…”
Section: Alternative Strategiesmentioning
confidence: 99%